A Comprehensive Review of the Versatile Dehydration Processes 2023
DOI: 10.5772/intechopen.108649
|View full text |Cite
|
Sign up to set email alerts
|

Food Dehydration Recent Advances and Approaches

Abstract: Dehydration of organic material is undoubtedly a controlled attempt to conserve or construct a novel construct that will satisfy functional devotions. Food dehydration is reviewed in light of the latest progress in food materials research. Understanding the mechanics behind the drying process is crucial in food and agricultural product dehydration. Among the most crucial steps in preserving food is dehydration. Food drying innovations include photovoltaic, thermal imaging, microwave-assisted, and comparable hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…Food spoilage is prevented by dehydrating it by reducing its moisture content, which inhibits bacterial growth and changes in chemicals. Besides preserving food microbiologically, this method also preserves its flavor and nutritional value (Riaz et al, 2022).…”
Section: Dehydrationmentioning
confidence: 99%
“…Food spoilage is prevented by dehydrating it by reducing its moisture content, which inhibits bacterial growth and changes in chemicals. Besides preserving food microbiologically, this method also preserves its flavor and nutritional value (Riaz et al, 2022).…”
Section: Dehydrationmentioning
confidence: 99%
“…According to previous studies health boosting potential of tea is mainly due to tea polyphenols Riaz et al, 2022). TPPs are well-known for their oxidative, anti-cancer, and other therapeutic characteristics (Mukhtar and Ahmad, 2000;Xing et al, 2019), but studies have shown that substantial amounts of tea are required to reap these advantages.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies health boosting potential of tea is mainly due to tea polyphenols (Yan et al, 2020;Riaz et al, 2022). TPPs are well-known for their oxidative, anti-cancer, and other therapeutic characteristics (Mukhtar and Ahmad, 2000;Xing et al, 2019), but studies have shown that substantial amounts of tea are required to reap these advantages.…”
Section: Introductionmentioning
confidence: 99%